Association between exercise and the risk of dementia: results from a nationwide longitudinal study in China. Issue 12 (4th December 2017) - Zhou, Zi; Fu, Jian; Hong, Y. Alicia; Wang, Ping; Fang, Ya
Abstract : Objective: This study was conducted to examine the causal association between exercise and the risk of dementia among older Chinese adults. Design: Longitudinal population-based study with a follow-up duration of 9 years. Setting: Data for the Chinese Longitudinal Healthy Longevity Survey waves occurring from 2002 to 2011–2012 were extracted from the survey database. Participants: In total, 7501 dementia-free subjects who were older than 65 years were included at baseline. Dementia was defined as a self-reported or proxy-reported physician's diagnosis of the disease. Outcome measures and methods: Regular exercise and potential confounding variables were obtained via a self-report questionnaire. We generated longitudinal logistic regression models based on time-lagged generalised estimating equation to examine the causal association between exercise and dementia risk. Results: Of the 7501 older Chinese people included in this study, 338 developed dementia during the 9-year follow-up period after excluding those who were lost to follow-up or deceased. People who regularly exercised had lower odds of developing dementia (OR=0.53, 95% CI 0.33 to 0.85) than those who did not exercise regularly. Conclusion: Regular exercise was associated with decreased risk of dementia. Policy-makers should develop effective public health programmes and build exercise-friendly environments for the general public.